Toxicogenic Fungi, Aflatoxins, and Antimicrobial Activities Associated with Some Spices and Herbs from Three Selected Markets in Ho Municipality, Ghana - Nii Korley Kortei; Barnabas Teye Djaba; Clement Okraku Tettey; Alfred Ofori Agyemang; Enoch Aninagyei; Edward Ken Essuman; Adjoa Agyemang Boakye; Theophilus Annan (International Journal of Food Science)
Spices and herbs are widely used food ingredients that enhance most organoleptic features of prepared foods. They are also used for medicinal and preservative purposes. Spices and herbs are potential carriers of bacteria, yeasts, and molds due to the nature of cultivation, harvest methods, storage conditions, packaging procedures, distribution, sale, and general handling. Although some fungi have been identified to be associated with most spices and herbs elsewhere in the world, little has been done on the presence of fungi in spices and herbs in Ghana. This study sought to identify the toxicogenic fungal profiles, mycotoxins (aflatoxins) present in some herbs, bay leaf (Laurus nobilis) and garden egg leaves (“gboma”) (Solanum macrocarpon), and spices, ginger (Zingiber officinale) and “dawadawa”(Parkia biglobosa), as well as to investigate the antimicrobial properties of the selected herbs and spices. The decimal reduction technique was used to plate onto Dichloran Rose Bengal Chloramphenicol (DRBC) agar media plates for fungal growth. Aflatoxin detection was carried out with high-performance liquid chromatographer connected to a fluorescence detector (HPLC-FLD). Antimicrobial properties were carried out using the agar diffusion method on solidified, freshly prepared Mueller-Hinton agar. A total of 12 species belonging to 7 genera, Aspergillus (niger, flavus, fumigatus, and ochraceus), Fusarium (oxysporum, verticillioides), Mucor (racemosus), Penicillium (digitatum, expansum), Rhizopus (stolonifer), Rhodotorula sp., and Trichoderma harzianum, were identified as fungal contaminants. Fusarium oxysporum was the most predominant species identified. Fresh ginger recorded the greatest number of colony-forming units (3.71 log10 CFU/g) with bay leaves recording the least number of colony counts (2.36 log10 CFU/g). Mycotoxin concentration detected in gboma was2.06±0.07 μg/kgand in dawadawa was2.13±0.09 μg/kg; however, mycotoxins were not detected in bay leaf and ginger. Ginger exhibited antibacterial activity against all bacteria ranging from 7.0±0.0 mm to 12.0±5.66 mm zones of inhibition. Ginger, bay leaf, and gboma extracts displayed fair antimicrobial activity against the bacteria investigated. On the other hand, dawadawa generally produced the least resistance against the five bacterial species but exhibited the highest zone of inhibition. All samples were slightly acidic with pH readings ranging from 5.81 to 6.76.